On selected family-group names in Chironomidae (Insecta, Diptera), and related nomenclature - Spies, Martin (Zootaxa, 2005)
The most relevant scientific names of subfamilies, tribes, and subtribes with extant members in Chironomidae are tabulated and discussed. Nomenclature is unified and stabilized, resulting in the following changed spellings or data. Family-group names: Boreoheptagyiini Brundin, 1966; Chironomidae Newman, 1834; Diamesinae Kieffer, 1922; Harrisonini Brundin, 1966; Heptagyiini Brundin, 1966; Macropelopiini ZavÍel, 1929; Pentaneurini Hennig, 1950; Podonominae Thienemann & Edwards in Thienemann, 1937; Protanypodini Brundin, 1956; Tanytarsini ZavÍel, 1917. Genus-group name: Zavrelia Kieffer, Thienemann & Bause in Bause, 1913. Species-group names: Lasiodiamesa serpentina Edwards & Thienemann in Thienemann, 1937; Zavrelia pentatoma Kieffer & Bause in Bause, 1913. Applications for rulings by the ICZN will be submitted to try to A) conserve Coelotanypodini Fittkau, 1962 in place of a senior synonym; B) fix the type species of Orthocladius van der Wulp, and conserve Orthocladiinae Kieffer, 1911 in place of two senior synonyms; C) fix the type species of Tanypus Meigen, and render Tanypodinae available from Kieffer (1906) rather than from Skuse (1889; type genus misidentified); and D) conserve Zavreliina Sæther, 1977 in place of a senior synonym.